Teacher - Student 1994. - Art Focus Contemporary Israeli Art, Jerusalem 1994 (Israel : Oranim College Art é Design Institute, 1994)
Shafran, Pola ; Segev, Mario ; Shachnai, Michal ; Kadosh, Yonit ; Rashelbach, Hovav ; Rehav, Roni ; Ringart, Dorit ; Efroni-Shenhar, Ornit ; Efroni, Hanny ; Israel (Roly) Netiv ; Nissim, Dafna ; Melamed, Noa ; Leibowitz, Pini ; Lopez, Ana ; Levi, Ami ; etc.
Teacher - Student 1994, "Oranim" College Art é Design Institute, Israel, 1994. Art Focus Contemporary Israeli Art, Jerusalem 1994
boek